Genetic gains for grain yield by irrigated rice breeding program in the Mid-North Region of Brazil - Rangel, Paulo Hideo Nakano; Pereira, José Almeida; Morais, Orlando Peixoto de; Guimarães, Elcio Perpétuo; Yokokura, Takumi (Pesquisa Agropecuaria Brasileira, 2000)
Data from 37 advanced yield trials, conducted from 1984 to 1997, were analyzed to evaluate the genetic progress made by the Brazilian Mid-north Region irrigated rice (Oryza sativa L.) breeding program. The following traits were measured: grain yield, days to flowering, plant height, and lodging. These trials had 89 breeding lines and two checks ('Cica 8' and 'Metica 1'). During these 14 years of experiments, the annual gain for grain yield was small and equal to 0.3%, but statistically significant (P < 0.05). The genetic correlations estimated by the conventional and indirect methods were similar. Out of the six cultivars recommended for the region during this period, the cultivar Diamante provided significant gains for grain quality, when compared to the checks.
Keywords: Oryza sativa; genetic gain; genetic correlation; genetic parameters; cultivars